Failure investigation on rear water wall tube of boiler - Ahmad J.; Purbolaksono J.; Beng L.C.; Rashid A.Z.; Khinani A.; Ali A.A. (2023)
This paper presents failure investigation on the SA210-A1 rear water wall tube by visual site inspection, tube wall thickness measurements and microscopic examination. The rear water wall tube has failed with wide open burst and was situated at the boiler nose lower bent region. On-site wall thickness measurements were performed on all the rear water wall tubes located at the same level of the ruptured tube. The tubes were observed to have experienced significant wall thinning. Microscopic examinations on the failed rupture region and some distance away region of the as-received tubes are also conducted in order to support in determining the failure mechanism and failure root cause. Failure mechanisms are discussed and the findings obtained from the site inspection, wall thickness measurements, microscopic examinations and creep analyses may finally reveal the failure mechanism and main root cause of the failure. The failure mechanism is identified as a result of the combination of the significant localized wall thinning of the rear water wall tube due to fly-ash erosion and a thermally activated process of creep problem due to increasing of temperatures. 2009 Elsevier Ltd. All rights reserved.